Student Perceptions of The Quality of Academic Services In Increasing Student Satisfaction In The Islamic Education Management Master’s Study Program FITK UIN North Sumatera Medan - Neliwati, Neliwati; SN, Abdullah Fikri Sholehuddin; Rabbirham, Rabbirham; Indriani, Yunisa (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to explore: First, student perceptions of the quality of academic services. Second, student satisfaction with academic services in the Master of Islamic Education Management Study Program, FITK UIN North Sumatra. This research method is a qualitative type with a phenomenological approach. The instruments used in this research were observation, interviews and documentation studies. The location of this research is the Master of Islamic Education Management study program, FITK UIN North Sumatra. This research data analysis uses three steps, data reduction, data presentation and conclusion drawing. The research results show that: First, there is a positive student perception of the quality of academic services related to correspondence administration services, KHS and KRS preparation services, placement of course lecturers. Meanwhile, for academic services related to the use of lecture facilities, students perceive that the provision of lecture facilities in accordance with lecture needs is not yet available. Second, student satisfaction with academic services has shown a sense of satisfaction in lectures, where students feel they have been well served in terms of administrative academic services. Even though there is still a feeling of dissatisfaction among students regarding the provision and use of lecture facilities that are not in accordance with lecture needs, for example, hampered internet networks, unavailability of information equipment, hot classrooms so that students and lecturers feel uncomfortable.